2019
DOI: 10.3390/ijerph16040603
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Diet and Physical Activity in Malaysian Adolescents: A Systematic Review

Abstract: The increased prevalence of unhealthy eating habits and sedentary lifestyles among Malaysian adolescents has become a public health concern. The aim of this systematic review was to summarize evidence from observational studies related to diet and physical activity (PA) among Malaysian adolescents (13–18 years) and to recognize the associations between determinants of diet and PA and diet and PA behaviours. A systematic search for observational studies published from August 1990 through August 2017 was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 59 publications
(158 reference statements)
2
24
1
Order By: Relevance
“…Additionally, we hand‐searched articles on the Sedentary Behaviour Research Network website (https://www.sedentarybehaviour.org/) and checked reference lists of relevant reviews . Furthermore, we requested for relevant studies on social media platforms; ResearchGate (social media network for scientists) and Twitter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we hand‐searched articles on the Sedentary Behaviour Research Network website (https://www.sedentarybehaviour.org/) and checked reference lists of relevant reviews . Furthermore, we requested for relevant studies on social media platforms; ResearchGate (social media network for scientists) and Twitter.…”
Section: Methodsmentioning
confidence: 99%
“…We performed searches in the following scientific databases: Medline org/) and checked reference lists of relevant reviews. 32,34,35,40,[46][47][48][49][50] Furthermore, we requested for relevant studies on social media platforms; ResearchGate (social media network for scientists) and Twitter. This allowed us to include studies until August 2019.…”
Section: Search Strategymentioning
confidence: 99%
“…The intervention was developed based on data obtained from systematic reviews ( 21 , 49 ), reports of the MyHeARTs cohort study ( 48 ), and a related qualitative study ( 50 ). The findings suggested that a school canteen intervention had merit.…”
Section: Methodsmentioning
confidence: 99%
“…Adolescents' dietary behaviour is likely to be strongly influenced by environmental factors (20,21). The school food environment is often considered as a target for nutritional intervention as school children consumed ∼40% of their daily dietary intake at schools (22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation